Use of civil construction waste for production of cementic mortar cobogó (Research, Society and Development, 2021)
The amount of construction waste deposited in landfill in Lorena city - SP is approximately 50 tons/day. This landfill is already at its limit capacity and represents an unusable area responsible for several environmental, economic and social impacts. The aim of this work is the development and characterization of a sustainable product from solid waste from civil construction. The morphology of the collected waste was analyzed by SEM/EDS. The residues were macerated, mixed in different proportions with cement and water, and made into rectangular boxes. The mechanical test was carried out by flexing three points on specimens, absorbing water and analyzing fracture by SEM. Morphology of samples showed a heterogeneous and porous mass, with particles of different sizes, few agglomerates, and the presence of organic material. Resistance to the average rupture of the samples was obtained in MPa, characteristic of concrete for structural application. This being so, a mockup was developed proposing a hollow element type product, Cobogó style, indicating the potential of using civil construction waste as a sustainable product.